IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DALAM MENINGKATKAN KETERAMPILAN PROSES DAN BERPIKIR KRITIS TENTANG IPA PADA SISWA KELAS VI SDN 01 KALUKUBULA - Supartayasa, I Gede Made (JSTT, 2014)
Process Skill and critical thinking regarding to natural science in  six grade  student of SDN 1 Kalukubula are still at lower level due to the teaching and learning activities have been using regular group or convensional model. This research implementing the cooperative model on STAD type in two cycles. The result of process skill classically increased from 74,58% at the first cycles to  81,67% on the second cycles. Meanwhile the result of critical thinking skill classically increased from 70,38% on the first cycles to 76, 88% on the second cycles. Students attitude toward group works in the second cycles also increased with the subjection mean 97,92%. The teacher activities in teaching and learning process have been done very well that is 100%. Based on learning these results,  it could be concluded that the implementation  of cooperative model on STAD type can improve the process skill and the critical thinking in pertinent to  science of elementary school students.